SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI TELADAN KEMENTERIAN AGAMA KABUPATEN DELI SERDANG DENGAN METODE ANALITIC HIERARCHY PROCESS - Ayu Prihatini; Sulindawaty Sulindawaty (JSIK (Jurnal Sistem Informasi Kaputama), 2020)
The absence of an exemplary employee election in the Ministry of Religion in Deli Serdang Regency has led to a decline in performance and performance of students. The ability to provide decision support systems is one of the interactive information systems that provide information, modeling and data manipulation. Decision support system for model employee selection is used not to substitute decisions, but support for decision making. Criteria set by the company in applying for credit are discipline, performance, commitment, responsibility and performance quality. With the AHP method, the criteria of interest intensity / priority scale are determined from the criteria. After carrying out the calculation process, the selection decision for employees and obtained from the ranking of the AHP method: 0.2669947 (rank 1), 0.25695721 (rank 2), 0.2446883 (rank 3), 0.229045 (rank 4). Keywords: motorcycle credit, SPK, AHP method.